Groundwater Potential of the Jakarta Groundwater Basin using the Darcy Equation Method - Imsak Aditya Respati Priyono; Thomas Triadi Putranto; Taat Setiawan (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2024)
The annual increase in population leads to a growing demand for water. To control groundwater utilization in a directed manner is to extract groundwater according to groundwater potential. The research aims to analyze the groundwater potential in the Jakarta Groundwater Basin in terms of quantity and quality. The method used is primary data analysis by determining quantity potential using the Darcy equation method with additional calculations of groundwater volume and quality potential based on drinking water quality standards from the Republic of Indonesia Minister of Health Regulation no. 2 of 2023 and WHO of 2022. The dynamic potential for unconfined aquifers ranges from 2,663–1,372,901 m³/year, while for confined aquifers range from 184,991–1,895,288 m³/year. The static potential for unconfined aquifers ranges from 266,852–3,252,654 m³, while for confined aquifers ranges from 1,317,862–30,620,266 m³. Based on groundwater quality standards for drinking water from the Minister of Health and WHO for the parameters pH, TDS, Na⁺, Cl⁻, SO₄²⁻ and NO₃⁻, there are 15 samples from 53 samples of unconfined aquifer and 36 samples from 75 samples of confined aquifer that meet standards.